AAMKS—Integrated cloud‐based application for probabilistic fire risk assessment. (18th June 2020) - Krasuski, Adam; Hostikka, Simo
Summary: Available models of fire risk assessment can still hardly be used for practical engineering problems. They are mostly loosely integrated, complex, computationally demanding applications, and require additional pre‐ or post‐hand‐calculations. However, the latest achievements in computer science enable establishing an easy‐to‐use web‐application with access to enormous computing power in a cloud requiring minimal management effort. In this article, we present a new tool for probabilistic fire risk assessment called Aamks. Our goal is to build an easy‐to‐use, science‐based, practical engineering tool to support building design in day‐to‐day work. To meet the overall goal, we aim at working out an integrated, web‐based application with computational efficiency and scalability allowed by cloud computing. Aamks performs a stochastic analysis of life safety in building fires using deterministic models for fire and evacuation and stochastic sampling of the uncertain input parameters.